في تعليم المفردات Number Head Together استخدام مدخل التعلم التعاوني بأسلوب: Penggunaan Model Pembelajaran Kooperatif Tipe Number Head Together dalam Pembelajaran Mufradat - Nyak Mustakim; Fadlina (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2021)
This study aims to determine the effectiveness of using the Numbered Heads Together (NHT) cooperative learning model in learning vocabulary at SD Negeri Blang Paseh. The method used by the researchers in this study was an experimental method with a two-group design (experimental and control). The data collection instruments used were observation, tests and documentation. The results of the study show that the use of the NHT cooperative learning model in vocabulary learning at Madrasah Ibtidaiyah Blang Paseh is effective in improving student learning outcomes, this is evidenced by the results of hypothesis testing and comparison of pretest and posttest scores for the two groups, as statistical results (t - count) = 3.686 is greater than the result of the table (t-table) = 1.664.